What Makes Johnny Run? Shaw’s “Man and Superman” as a Pre-Freudian Dream Play - Weintraub, Rodelle (ABEI Journal, 2003)
Long before Freud was heard of,” Bernard Shaw wrote to a friend in 1934, a generation after he had written Man and Superman, (1901-1903), “I held that Nature had introduced an element of antipathy into kinship as a defence against incest.” Although Man and Superman appears to be a late-Victorian comedy about love and money and Shaw’s philosophy of the Life Force, one of the driving forces that impels both the manifest play and the latent dream play is the incest taboo. It is a taboo which is so universal and so strong, that it affects persons who have brother-sister and parent-child relationships, even if they are not actually family members. Ann Whitefield is determined to have as her mate, her first love, John Tanner. Tanner knows he has long loved her and still does. But his terror at having any sexual relationship with her is far stronger than his ardor. For much of the first two acts, Ann manipulates and tempts John as their relationship changes from brother-sister to father-daughter and then pursued lover and determined pursuer. At some point between Act 2 and Act 3, while Tanner and his chauffeur Straker are racing through France and Spain, Tanner falls asleep and the remainder of the play takes place on two levels: the manifest play which includes the literary dream sometimes played separately as “Don Juan in Hell” and the latent dream play in which Tanner’s fear of incest is resolved and he is finally able to accept himself not as Ann’s brother but as her future husband.